Nutritional status and metabolic alterations in patients with ataxia-telangiectasia - Cristiano do Amaral de Leon; Sérgio Luis Amantea; Renan Augusto Pereira; Ellen O. Dantas; Jéssica Loekmanwidjaja; Beatriz T. Costa-Carvalho; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. González-Serrano; Elizabeth Alejandra De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Ataxia-telangiectasia (A-T) is a DNA repair disorder characterized by progressive degeneration, immunodeficiency, cancer predisposition, malnutrition, metabolic disorders, and chronic liver disease. The study aims to describe the nutritional status and plasma levels of biomarkers of lipid status, metabolic profile, and liver function of patients with A-T. Results A total of 218 patients from 9 Latin American countries were included in the study. The distribution of patients according to nutritional status by age group revealed an over-time increase in the proportion of patients with severe thinness (p = 0.016). High glucose and triglyceride levels were observed in 9.5% and 23.6% of patients, respectively. Total cholesterol was high in 31.7, and 34.0% had abnormal LDL-c levels. In the analysis of paired samples, a progressive increase in aspartate aminotransferase was observed over time. Conclusions The present results are comparable to those of previous studies also showing changes in nutritional status and in lipid, metabolic, and liver profiles over time. These findings confirm a high rate of thinness in patients with A-T and progressive deterioration as the disease progresses, as well as changes in plasma levels of biomarkers of lipid status, metabolic profile, and liver function.